Study of Inundation Management on Tertiary Drainage Channels in Keputih Tegal Surabaya City - Dyan Eka Nurhayati; Jenny Caroline; Dewi Kusumaningrum (Journal of Civil Engineering, Planning and Design, 2022)
In the case of heavy rain, several places in Surabaya are still submerged. The Keputih Tegal region is one of them. The Jalan Keputih Tegal channel is a tertiary drainage channel that drains into a secondary drainage channel on Jalan Raya Keputih before emptying into the Wonokromo river. The flood on Jalan Keputih Tegal occurred at a depth of 20 cm. The drainage channel on Jalan Keputih Tegal is the subject of this study, and the data utilized are secondary data in the form of rainfall data collected from the Public Works Department of Highways Surabaya and the SDMP (Surabaya Drainage Master Plan) map obtained from BAPPEKO Surabaya. The dimensions of the channel are 1.5 x 1.5 m with a capacity of 0.9 m3/s based on the flood flow from the CA region and the drainage system of the Keputih Tegal channel, which is impacted by the height of the secondary channel MAB. The channel's proportions allow for both flood discharge and backwater discharge. With a flow velocity of 0.4 m/s, the channel slope is planned to be 0.04 percent. This condition exceeds the allowed speed criteria for concrete channels, which are 1.5 m/s.